2019
DOI: 10.1155/2019/9512406
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BSF on Podocyte Apoptosis via Regulating the ROS-Mediated PI3K/AKT Pathway in DN

Abstract: Diabetic nephropathy (DN) is the leading cause of end-stage renal disease (ESRD). The ROS-mediated PI3K/AKT pathway plays a key role in podocyte apoptosis and DN progression. Our previous study demonstrated that Baoshenfang (BSF) can decrease proteinuria and attenuate podocyte injury. However, the effects of BSF on podocyte apoptosis induced by the ROS-mediated PI3K/AKT pathway remain unclear. Herein, in vivo and in vitro studies have been performed. In our in vivo study, BSF significantly decreased 24-h urina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…The PI3K/Akt signaling pathway is widely present in eukaryotic cells and participates in many physiological and pathological processes, such as cell growth, differentiation and proliferation. Studies have shown that in some disease states, stabilizing the PI3K/Akt signaling pathway can effectively alleviate damage to podocytes and reduce the incidence of proteinuria [15][16] .In recent years, studies have found that there are functional receptors for glucocorticoids in podocytes,and glucocorticoids can directly act on podocytes to protect them [17][18][19][20] . Glucocorticoids can mediate the activation of the PI3K/Akt pathway, inhibit cell apoptosis through a variety of mechanisms, and promote cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt signaling pathway is widely present in eukaryotic cells and participates in many physiological and pathological processes, such as cell growth, differentiation and proliferation. Studies have shown that in some disease states, stabilizing the PI3K/Akt signaling pathway can effectively alleviate damage to podocytes and reduce the incidence of proteinuria [15][16] .In recent years, studies have found that there are functional receptors for glucocorticoids in podocytes,and glucocorticoids can directly act on podocytes to protect them [17][18][19][20] . Glucocorticoids can mediate the activation of the PI3K/Akt pathway, inhibit cell apoptosis through a variety of mechanisms, and promote cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…The results of metabolite analysis of the urine show that there were 287 specific metabolic biomarkers that distinguished among the YSHS, DN, and normal groups, and a total of 171 pathways were involved, and the genes were binned into diabetic nephropathy pathways like the glucagon signaling pathway, insulin secretion, insulin resistance, insulin signaling pathway, etc. There are some differences between the pathway analyzed by metabolomic study and the pathway analyzed by network pharmacology, but there are some hints that the changes are related to insulin resistance, and PI3K and Akt are key insulin signaling molecules in the body, which have significant regulatory effects on glucose and DN progression (Cui et al, 2019). It was verified in the present study that YSHS significantly inhibited the phosphorylation of PI3K/AKT/mTOR, thereby delaying the progression of DN.…”
Section: Discussionmentioning
confidence: 50%
“…As the main component of EH, quercetin has been proved to improve renal fibrosis and apoptosis in chronic renal failure rats, as well as reducing water retention and toxin accumulation by inhibiting the PI3k/Akt pathway through targeting PIK3R [ 53 ]. Thus, regulating the PI3K/AKT pathway in podocytes through EH may be an important potential targeted therapy for NS in the future [ 54 ]. As one of important inflammatory pathways, the TNF signaling pathway plays a central role in the regulation of different cellular events such as immunity, apoptosis, cell proliferation, and differentiation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%